2021
DOI: 10.47970/jml.v4i2.238
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Service Quality Improves Brand Image in Hotels Xyz: Word of Mouth as a Mediation

Abstract: This study aims to analyze the effect of service quality on the brand image through word of mouth at Hotel XYZ Jakarta. The population in this study were all guests who came to the Hotel XYZ Jakarta, using primary data obtained from questionnaires with the accidental sampling method. Data samples were obtained from 234 respondents at Hotel XYZ in Jakarta. This study uses non-probability sampling with the SEM method, which is processed by SPSS and SmartPLS programs. The results represent service quality has a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The result indicated a positive effect of service quality on brand image. Other studies also showed a positive effect of service quality on brand image of hotels but through word of mouth (Nainggolan and Amidiola, 2021).Another study on Malaysian resort hotels reported a lucrative physical environment develops better positive image. Further developing a good service image has a potential impact on repeat purchase and profit making (Hu et.…”
Section: Service Quality Effect On Brand Name and Brand Imagementioning
confidence: 90%
“…The result indicated a positive effect of service quality on brand image. Other studies also showed a positive effect of service quality on brand image of hotels but through word of mouth (Nainggolan and Amidiola, 2021).Another study on Malaysian resort hotels reported a lucrative physical environment develops better positive image. Further developing a good service image has a potential impact on repeat purchase and profit making (Hu et.…”
Section: Service Quality Effect On Brand Name and Brand Imagementioning
confidence: 90%